PENGUATAN NILAI PANCASILA PADA SISWA SEKOLAH DASAR SEBAGAI UPAYA MEMBANGUN NASIONALISME DI TENGAH ERA GLOBALISASI - Qinwan Nishrina Nurul Bayani; Dinie Anggraeni Dewi; Muhammad Irfan Ardiansyah (Social Sciences Journal, 2023)
Abstract The loss of the nationalist spirit in society in the era of globalization has resulted in the erosion of Pancasila's identity as a way of life and ideology of the Indonesian nation. The behavior of society which is increasingly far from the moral values of Pancasila is forming a similar generation of young people. Individualistic, apathetic attitudes and being immersed in foreign culture are the result of the negative impacts of globalization. Indonesian society has lost a generation that had a spirit of nationalism. This is certainly a serious challenge for the Indonesian nation to re-instill the values of Pancasila in each individual. An effort needs to be made to overcome this problem, namely by saving the younger generation from the negative influence of globalization which threatens national identity. Strengthening Pancasila values carried out in the younger generation from an early age, namely elementary school age, can be a prevention for reviving a young generation with a nationalist spirit and behavior that is reflected in the values of Pancasila as the nation's ideology and way of life. Keywords: Pancasila, Values of Pancasila, Nationalism, Globalization, Elementary School Abstrak Hilangnya sikap nasionalisme di tengah masyarakat pada era globalisasi mengakibatkan terkikisnya jati diri Pancasila sebagai pandangan hidup serta ideologi bangsa Indonesia. Perilaku masyarakat yang semakin jauh dari nilai-nilai moral Pancasila membentuk generasi muda yang serupa. Sikap individualis, apatis, serta tenggelam dalam budaya asing merupakan dampak negatif globalisasi. Masyarakat Indonesia telah kehilangan generasi yang memiliki jiwa nasionalisme. Hal ini tentu menjadi tantangan yang serius bagi Bangsa Indonesia untuk menanamkan kembali nilai-nilai Pancasila pada setiap individunya. Perlu dilakukan sebuah upaya untuk mengatasi permasalahan tersebut yaitu dengan menyelamatkan generasi muda dari pengaruh negatif globalisasi yang mengancam jati diri bangsa. Penguatan nilai Pancasila yang dilakukan pada generasi muda sejak dini yaitu usia sekolah dasar dapat menjadi sebuah upaya pencegahan untuk menghidupkan kembali generasi muda yang berjiwa nasionalis serta memiliki perilaku yang tercermin dari nilai-nilai Pancasila sebagai ideologi serta pandangan hidup bangsa. Kata Kunci: Pancasila, Nilai-nilai Pancasila, Nasionalisme, Globalisasi, Sekolah Dasar